The Effects of an 8-Week Strength Training Toward the Specific Preparation Phase on Male Volleyball Athletes’ Performance - Arjuna, Fatkurahman; Pamungkas, Gallant; Primasoni, Nawan; Rahayu, Tri Winarti (Physical Education Theory and Methodology, 2024)
Background. Training programs are part of training management that need to be properly and correctly prepared and implemented. Study Purpose. The aim of the study was to evaluate the effects of an 8-week program of resistance training, carried out at a specific preparation phase, on the performance of male junior volleyball athletes. Materials and methods. This study was conducted as experimental research, with a sample of 24 male volleyball athletes ([mean ± SD] age: 17.96 ± 1.23 years; body weight: 75.56 ± 7.80 kg; height: 180.46 ± 7.14 cm; body fat: 17.62 ± 3.36%) who were randomly divided into experimental group (EG): n = 12 and control group (CG): n = 12. The training program lasted for eight weeks and took place at a specific preparation phase. Results. There was a significant increase in the indicators handgrip dynamometer left (p<0.014), handgrip dynamometer right (p<0.001), vertical jump (p<0.001), sit-and-reach test (p<0.000), leg dynamometer (p<0.000), and back dynamometer (p<0.001) in the experimental group after being given strength training treatment for eight weeks. Conclusions. When strength training is included in volleyball training, it can increase the performance in power, strength, and flexibility, especially when carried out at a specific preparation phase. Incorporating targeted stimuli, such as strength training, into training sessions appears to be a secure method of training for this age group and may help to contribute to continuous and gradual improvements in neuromuscular adaptation.